PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEWUJUDKAN LINGKUNGAN BELAJAR YANG INKLUSIF - widyahati, sri; Hasani, Melisa; Puspika Sari, Herlini; Nasution, Zikri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to examine the role of Islamic Religious Education (IRE) teachers in creating aninclusive learning environment. IRE teachers are not only knowledge facilitators but also agents ofcharacter development who instill values of tolerance, mutual respect, and empathy. In the context ofinclusive education, IRE teachers are expected to foster a fair and welcoming atmosphere for allstudents regardless of religious, cultural, social, or individual ability differences. This researchemploys a qualitative approach using library research to explore the contributions of IRE teachers inshaping an inclusive educational ecosystem. The findings indicate that active teacher involvement inapplying inclusive principles through adaptive teaching methods, humanistic approaches, andexemplary conduct can lead to a more harmonious learning environment that bridges differences.These insights offer valuable input for strengthening educational practices that embrace diversity andpromote social justice.